2020
DOI: 10.3390/ma13071755
|View full text |Cite
|
Sign up to set email alerts
|

Uniaxial Tensile Strain Induced the Enhancement of Thermoelectric Properties in n-Type BiCuOCh (Ch = Se, S): A First Principles Study

Abstract: It is well known that the performance of thermoelectric measured by figure of merit ZT linearly depends on electrical conductivity, while it is quadratic related to the Seebeck coefficient, and the improvement of Seebeck coefficient may reduce electrical conductivity. As a promising thermoelectric material, BiCuOCh (Ch = Se, S) possesses intrinsically low thermal conductivity, and comparing with its p-type counterpart, n-type BiCuOCh has superior electrical conductivity. Thus, a strategy for increasing Seebeck… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…In the literature, Zou et al. found that application of 6% uniaxial tensile strain along the c direction can significantly improve the power factor by 54% for n‐type BiCuOSe and by 74% for n‐type BiCuOS at 800 K 65 . The enhancement can be attributed to the significantly enhanced Seebeck coefficient resulting from the increased electron effective mass 65 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature, Zou et al. found that application of 6% uniaxial tensile strain along the c direction can significantly improve the power factor by 54% for n‐type BiCuOSe and by 74% for n‐type BiCuOS at 800 K 65 . The enhancement can be attributed to the significantly enhanced Seebeck coefficient resulting from the increased electron effective mass 65 .…”
Section: Resultsmentioning
confidence: 99%
“…This is different from the cases of BiCuOCh (Ch = S, Se, Te). In the literature, Zou et al found that application of 6% uniaxial tensile strain along the c direction can significantly improve the power factor by 54% for n-type BiCuOSe and by 74% for n-type BiCuOS at 800 K. 65 The enhancement can be attributed to the significantly enhanced Seebeck coefficient resulting from the increased electron effective mass. 65 This differs from the case of n-type doped LaCuOSe, for which the power factor is reduced under 5% and 10% tensile strain.…”
Section: F I G U R Ementioning
confidence: 99%
See 1 more Smart Citation